Optimization of Medium Voltage Distribution Network Maneuver for Feeder Reliability in Fault Conditions - Risnandar, Muhammad Aris; Faridah, Linda; Nurdiansyah, Rian (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2025)
Network maneuvers in the medium voltage distribution system are performed during faults or maintenance to maintain continuity of electricity service. This study focuses on analyzing the network conditions during maneuvers in the Tasikmalaya area to identify the optimal feeder backup strategy and minimize voltage drops and power losses. The analysis was conducted using ETAP software with simulations of various load scenarios (40%, 80%, and 100%). The results show that the best voltage in the existing condition is found on the SBBC feeder, with a voltage value of 0.9710 p.u at a 100% load condition. Meanwhile, the smallest power losses occur on the TMSR feeder, amounting to 233.6 kW. In the maneuver scenario, the best results are obtained when the TMSR feeder is backed up by the PDYN feeder through the LBS RIMA switch, with a voltage of 0.9612 p.u on the TMSR feeder and 0.9533 p.u on the PDYN feeder, and total power losses of 606.6 kW. This study highlights the importance of in-depth analysis in selecting maneuver strategies to ensure network stability and minimize service disruptions. The decision to choose a backup feeder should not only consider the feeder's ability to support additional loads but also its impact on power losses and voltage quality across the network. Therefore, this research makes a significant contribution to more efficient medium voltage distribution network management, particularly in handling faults and maintenance.